Analisis Keyakinan Diri (Self-efficacy) Mahasiswa Universitas Tidar terhadap Perangkat Lunak SPSS - Zahra, Irena Devia; Mawarni, Aruming Sekar; Susilowati, Susilowati; Manasikana, Arina; Nugraha, Joko Tri (ANTASENA: Governance and Innovation Journal, 2025)
The Statistical Package for the Social Sciences (SPSS) application plays a crucial role in research activities at universities for analyzing quantitative data. However, the level of students' confidence in operating this software still varies, influenced by factors such as statistical knowledge, practical experience, and learning support. Therefore, this study aims to describe the level of self-efficacy of Tidar University students regarding the use of SPSS and the factors that influence it, in response to the importance of mastering statistical analysis tools in preparing final assignments and scientific research. This research uses a descriptive quantitative approach, with data collection techniques thru online questionnaires completed by 50 respondents who are students in the Public Administration Study Program at Tidar University. Data analysis was performed using descriptive statistics thru SPSS. The research results show that the majority of students have a high level of confidence in using SPSS. This increase in confidence is particularly significant when they receive assistance in the form of facilities, training, direct guidance, and adequate time allocation to complete their work. Additionally, prior experience using SPSS or similar software and a basic understanding of statistical concepts also contributed to boosting their confidence. Overall, this research concludes that the level of confidence among Tidar University students regarding the use of SPSS falls into the high category. These findings underscore the urgency of practice-focused training, ongoing mentorship, and the availability of a supportive academic environment in building students' self-efficacy regarding the use of SPSS for study purposes and scientific research activities.